RINGKASAN HASIL PENELITIAN: PERTUMBUHAN DAN PEMBANGUNAN DI SUB-SAHARA AFRIKA: PENGALAMAN ETHIOPIA - Muzzar Kresna; Saiful Hakam; Ahmad Helmy Fuady; Erwiza Erman (Jurnal Kajian Wilayah, 2018)
Ethiopia’s economy heavily depending on agriculture sector, especially coffee. Though the rapid rate of economic growth since 2004 has been due to an increase in the service sector and industry (mainly construction and energy). To sustain its economic growth, Ethiopia adopted several policy strategies including: developing light manufacturing industries (garments, leather products and footwear) by utilizing the Africa Growth & Opportunity Act (AGOA) scheme, developing Ethiopian Airlines airlines, utilizing the Africa Single Aviation Market scheme, and the construction of a Dry Port. Meles Zenawi's understanding of the developmental state model embodied in infrastructure-based development is not only supported by international institutions such as the World Bank and African Development Bank but also encouraged by China's increasing role in Africa. Not surprisingly, the level of infrastructure development in Ethiopia, such as roads, railroads, bridges, power plants and irrigation channels, has risen sharply with funding from multilateral and bilateral donors, especially with China's involvement in its development. Compared to other countries, Ethiopia has benefited because of its relationship with China, especially with the shift in global economic power after the global financial crisis. This research seeks to explain how economic growth and development in Ethiopia is caused by changes in development orientation in the country.Keywords: infrastructure, economic growth, ChinaAbstrakEthiopia merupakan negara dengan basis perekonomian adalah sektor pertanian, terutama komoditas kopi. Tetapi, pesatnya tingkat pertumbuhan ekonomi sejak tahun 2004 lebih disebabkan oleh peningkatan sektor jasa dan industri (terutama konstruksi dan energi). Untuk menopang pertumbuhan ekonominya, Ethiopia menempuh beberapa strategi kebijakan antara lain: pengembangan industri manufaktur ringan (garmen, produk kulit dan alas kaki) dengan memanfaatkan skema  Africa Growth & Opportunity Act (AGOA), pengembangan maskapai Ethiopian Airlines, pemanfaatan skema Africa Single Aviation Market, dan pembangunan Dry Port.  Pemahaman Meles Zenawi tentang model developmental state yang diwujudkan dalam pembangunan berbasis infrastruktur, tidak hanya didukung oleh lembaga internasional seperti World Bank dan African Development Bank, namun juga didorong dengan naiknya peran China di Afrika. Tidak mengherankan tingkat pembangunan infrastruktur di Ethiopia, seperti jalan raya, rel kereta, jembatan, pembangkit listrik, dan saluran irigasi meningkat tajam dengan pendanaan dari donor multilateral dan bilateral, terutama dengan keterlibatan China dalam pembangunannya. Dibandingkan dengan negara-negara lain, Ethiopia menjadi negara yang diuntungkan karena hubungannya dengan China, terutama dengan pergeseran kekuatan ekonomi global setelah adanya krisis finansial global. Penelitian ini berusaha menjelaskan bagaimana pertumbuhan dan pembangunan ekonomi di Ethiopia disebabkan oleh perubahan orientasi pembangunan di negeri tersebut.Kata kunci: Infrastruktur, pertumbuhan ekonomi, China